Moral distress experienced by nurses: A quantitative literature review. (February 2015) - Oh, Younjae; Gastmans, Chris
Nurses are frequently confronted with ethical dilemmas in their nursing practice. As a consequence, nurses report experiencing moral distress. The aim of this review was to synthesize the available quantitative evidence in the literature on moral distress experienced by nurses. We appraised 19 articles published between January 1984 and December 2011. This review revealed that many nurses experience moral distress associated with difficult care situations and feel burnout, which can have an impact on their professional position. Further research is required to examine worksite strategies to support nurses in these situations and to develop coping strategies for dealing with moral distress.